(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Trigeminal neuralgia also known as ‘Fothergill’s disease’ or ‘tic douloureux’ is a very peculiar disease. The severe pain is paroxystic and can be triggered by a mild cutaneous stimulus on the face or “trigger zone”. The disease has a wide variety of etiology and clinical presentation. The management will include both medical and a surgical approach. A 58-year-old female patient had reported with a complaint of pain for 8 years. On thorough history taking and clinical examination, we were able to confirm the final diagnosis as trigeminal neuralgia (TN). We present a case of trigeminal neuralgia of the maxillary and mandibular division along with clinical history, MRI (Magnetic Resonance Imaging) findings and treatment approach. Bang. J Neurosurgery 2019; 8(2): 105-107